Leveraging RNA interference technology for selective and sustainable crop protection - Qi, Hong-Yue; Zhang, Dan-Dan; Liu, Binhui; Chen, Jie-Yin; Han, Dongfei; Wang, Dan (Frontiers in Plant Science, 2024)
Double-stranded RNA (dsRNA) has emerged as key player in gene silencing for the past two decades. Tailor-made dsRNA is now recognized a versatile raw material, suitable for a wide range of applications in biopesticide formulations, including insect control to pesticide resistance management. The mechanism of RNA interference (RNAi) acts at the messenger RNA (mRNA) level, utilizing a sequence-dependent approach that makes it unique in term of effectiveness and specificity compared to conventional agrochemicals. Two primary categories of small RNAs, known as short interfering RNAs (siRNAs) and microRNAs (miRNAs), function in both somatic and germline lineages in a broad range of eukaryotic species to regulate endogenous genes and to defend the genome from invasive nucleic acids. Furthermore, the application of RNAi in crop protection can be achieved by employing plant-incorporated protectants through plant transformation, but also by non-transformative strategies such as the use of formulations of sprayable RNAs as direct control agents, resistance factor repressors or developmental disruptors. This review explores the agricultural applications of RNAi, delving into its successes in pest-insect control and considering its broader potential for managing plant pathogens, nematodes, and pests. Additionally, the use of RNAi as a tool for addressing pesticide-resistant weeds and insects is reviewed, along with an evaluation of production costs and environmental implications.